Politik Identitas, Ancaman Demokrasi dan Ketahanan Nasional Jelang Pilpres 2024 - Apriando, Alexander; Ridho Akustyo, Bagus; Miardi, Miardi; Agustina, Saur Martha (Jurnal Kajian Stratejik Ketahanan Nasional, 2023)
National resilience requires a mature political system and democracy. One of the indicators of good democratic development is pluralism and political participation. A healthy democracy undoubtedly ensures that all parties can participate fairly in politics. The social diversity present in Indonesia allows for the politicization of a social identity for the sake of winning political contests, which is feared to become a source of conflict threatening our national resilience through security instability. The impact of identity politics was strongly felt during the gubernatorial election in Jakarta a few years ago. Indonesia is certainly undergoing democratic maturity and does not wish for such events to be repeated in the upcoming 2024 presidential election contest. This writing will describe the potential use of identity politics in the 2024 presidential election. By conducting a literacy study from various sources, the authors will analyze the possibilities related to the use of social identity as a campaign tool in the 2024 presidential election by the contestants and the potential for conflicts that may arise.